Rancang Bangun Aplikasi Website Percetakan Printop Pada Modul Costumer Dan Editor Dengan Metode Pengembangan Waterfall - Fiqryansyah, Muhammad Rizky; Hermawan, Indra (Jurnal Teknologi Terpadu, 2020)
The design of a printing application aims to serve customers online in the printing business. This application is in the form of a website to facilitate integration between data and exchange information between customers and employees at Printop printing. Customers can determine the specifications for the products they choose according to their needs. The results of this design to become an application are expected to be a way to simplify the ordering process and be a solution in minimizing the density of visitors at the printing location when orders are getting busy. For customers' convenience, they do not have to wait for the processing time in the immediate place; besides that, the customer can order it anywhere. The test was carried out using a BlackBox, and the score was 90.69%, and the user acceptance test was 90%. Based on the test results, it can be concluded that the application is running functionally, and according to user needs.